1999
DOI: 10.1074/jbc.274.37.25983
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Miniature Plasma Membrane Ca2+ Channel Imin by Inositol 1,4,5-Trisphosphate Receptors

Abstract: I min is a plasma membrane-located, Ca 2؉ -selective channel that is activated by store depletion and regulated by inositol 1,4,5-trisphosphate (IP 3 ). In the present work we examined the coupling between I min and IP 3 receptors in excised plasma membrane patches from A431 cells. I min was recorded in cell-attached mode and the patches were excised into medium containing IP 3 . In about 50% of experiments excision caused the loss of activation of I min by IP 3. In the remaining patches activation of I min by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
40
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 21 publications
5
40
0
Order By: Relevance
“…3) are all highly reminiscent of recently described effects of PIP 2 Ab and PIP 2 on intracellular InsP 3 R (23). We recently demonstrated direct I min -InsP 3 R functional coupling (12). The data described in the present report can be explained under the assumption that the I min in A431 cells are directly coupled to InsP 3 R-PIP 2 complexes proposed to exist underneath the plasma membrane (Fig.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…3) are all highly reminiscent of recently described effects of PIP 2 Ab and PIP 2 on intracellular InsP 3 R (23). We recently demonstrated direct I min -InsP 3 R functional coupling (12). The data described in the present report can be explained under the assumption that the I min in A431 cells are directly coupled to InsP 3 R-PIP 2 complexes proposed to exist underneath the plasma membrane (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…Evidence for a "conformational coupling" model comes from the highly compartmentalized connection between InsP 3 -induced Ca 2ϩ release and Ca 2ϩ influx processes (15)(16)(17)(18)(19). Direct InsP 3 R-I CRAC conformational coupling has been experimentally supported by recent data obtained with recombinantly expressed mammalian trp channels (20 -22) and with I min in human carcinoma A431 cells (12).…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Several studies also have suggested that Trp3 activation involves interaction with underlying IP 3 Rs or, in some instances, ryanodine receptors (34)(35)(36). There is also evidence that CCE may involve such an interaction (37,38), in support of the proposed conformational coupling model for the regulation of SOCs (7,8). Thus, despite the fact that expressed Trp3 apparently is not regulated by store depletion, its interaction with IP 3 Rs has been investigated as a model for understanding the conformational coupling mechanism.…”
mentioning
confidence: 99%